P49 An economic evaluation of a complex workplace dietary intervention: a cluster controlled trial. (2nd September 2017) - Fitzgerald, S; Murphy, A; Kriby, A; Geaney, F; Perry, IJ
Abstract : Background: The workplace is recognised as a priority environment to influence dietary behaviours and improve employee healthy. Yet, previous workplace dietary interventions have failed to combine clinical effectiveness evidence with economic costs, thus the cost-effectiveness of workplace dietary interventions remains unknown. Employing cost and outcome data from the Food Choice at Work (FCW) study, a cluster controlled trial of complex workplace dietary interventions, this study employed an economic evaluation of nutrition education, environmental dietary modification and combined workplace interventions. Methods: A 9 month time horizon was assumed (length of interventions). Each of the dietary interventions (education, environment and combined) were compared to a control workplace. Firstly, a cost-benefit analysis (CBA) employed the monetary value of absenteeism to report the net benefit of the interventions compared to the control, from an employer's perspective. Secondly, cost-effectiveness analyses (CEAs) were performed using intervention-specific clinical measures (body mass index (BMI), weight and midway waist circumference) to measure health outcomes. Thirdly, a cost-utility analysis (CUA) measured the cost-effectiveness of the interventions in terms of quality adjusted life years (QALYs). The robustness of the QALYs were assessed as the results of the CEAs and CUA were compared. Probabilistic sensitivity analysis (Monte Carlo simulation) assessed parameter uncertainty. Results: The environment intervention reported the highest net benefit (€146/employee) which was associated with an average reduction of 0.7 absent days. The environment intervention also reported the lowest incremental cost-effectiveness ratios (ICERs) for BMI (€14/kg/m 2 ), waist circumference (€3/cm) and weight (€7/kg). The CUA demonstrated similar results as the environment intervention also reported the lowest ICER of €98/QALY, followed by the education (€971/QALY) and combined interventions (€2, 156/QALY). The cost-effectiveness acceptability curve (CEAC) indicated that the environment intervention had a 50% probability of being cost-effective when compared to the control at a ceiling ratio of €45, 000/QALY. However, as demonstrated on the CEAC, no decision uncertainty surrounded the cost-effectiveness of the education or combined interventions, the control had a higher probability of being cost-effective. Conclusion: Although demonstrated over a short timeframe, environmental dietary modification alone, offers a potentially cost-effective approach for improving employee health and generating positive net benefit for employers. While environmental dietary modification strategies are potentially sustainable and important interventions for obesity prevention, future research should include long-term outcomes to determine if improvements in outcomes persist.